Percepção de cientistas e da história da ciência em livros didáticos de química - Leske, Gabriele (2017)
The images of scientists and the History of Science (HC) presented in textbooks (LDs) of chemistry are also part of the school knowledge about Science, we believe that these can influence students realize the story of scientists as a result of work influenced by social, cultural and political contexts consistent with the era in which they lived. In this sense, the problem of this research is to analyze the perceptions of students on the images of a scientist and the history of science in textbooks of chemistry, indicated by the Textbook Guide National Textbooks Program (PNLD – Programa Nacional de Livros Didáticos) (2014) 2015. We Select all pictures of scientists and historical approaches of 4 (four) textbooks intended for the 1st (first) grade of high school. For analysis of perceptions, we use the Vygotsky's Sociocultural Theory and, in a first step, we conduct an individual activity and writing, in which the same image and text that accompanies that image was observed for 3 students. In a second step, we use the methodology of Focus Group (FG) with audio and video recording. The lines of the GF and individual writings were transcribed and your content has been parsed according to assumptions of the analysis of Bardin’s (2011) content. As results point that students realized general characteristics of the image and textual elements on HC, including: gender, age, clothing, actions of the scientist, environment in which he finds himself, scientific theories and social recognition. In addition, they realized aspects relating to the exposure of the scientist in LD, among them, the shape of image display in LD and the relation between image and text. The data refer to the suggestions about configuration mode of the image of the scientist and the history of science texts accompanying the invited person; the contextualization scientific production; the characteristics of internal and outside approaches of science.